Priority Populations Toolkits: Enhancing researcher readiness to work with priority populations - Kevin Rak; Alicia K. Matthews; Gabriela Peña; Wendy Choure; Raymond A. Ruiz; Sandra Morales; Amparo Castillo; Jackie Soo; Emily E. Anderson (Journal of Clinical and Translational Science, 2020)
The National Center for Advancing Translational Sciences has called for more comprehensive research with priority populations to reduce disparities and for the development of additional resources to assist researchers in implementing these recommendations. Here we report the development and initial evaluation of five Priority Populations Toolkits, which are resources developed by the University of Illinois Center for Clinical and Translational Science to meet these goals. Three aims guide the content: increasing knowledge, facilitating communication, and improving research design. Materials were curated from scientific literature reviews and Internet searches and revised iteratively. Analytics and user surveys provide information about usage. In 22 months, 387 unique users accessed the toolkits. The top reason for usage was to improve research recruitment. Comprehensive toolkits for working with priority populations show promising potential for increasing knowledge and readiness to work with underrepresented populations. Further toolkit development and evaluation of effectiveness are warranted.